Nonsurgical management of upper eyelid retraction in thyroid eye disease - Stephanie Ming Young; Yoon-Duck Kim; Kyung In Woo (Taiwan Journal of Ophthalmology)
Upper eyelid retraction (UER) is the most common sign of thyroid eye disease (TED) and may result in lagophthalmos and exposure keratopathy. Measures to address UER are varied and include conservative treatment, surgical intervention, and injections of botulinum toxin, hyaluronic acid (HA) filler, and triamcinolone acetonide (TA). Our article will discuss the various nonsurgical aspects of managing TED-related UER, focusing on the injections of botulinum toxin, HA filler, and TA to the upper eyelid, which have all been reported to be effective in improving UER in both active and inactive states of TED. Individual response may vary, and repeated injections may be necessary.